Determinants of bank liquidity in Zimbabwean commercial banks (2010-2014). - Musarurwa, Wadzanai E. (Midlands State University, 2017)
Zimbabwe is facing interwoven economic challenges, to the extent that financial distress amongst banks has been rampant owing to perennial liquidity constraints. The research focus was on identifying the determinants of bank liquidity for commercial banks in Zimbabwe during dollarization. The broad categories of determinants of liquidity entail the bank-specific factors and macroeconomic factors. The research adopted an explanatory research design and 16 commercial banks were used as the research subjects. Secondary data was obtained from the audited financial statements of banks, ZIMSTAT, RBZ monthly economic review reports and the monetary policy. Data collected covered the period from 2010 to 2014 and was analyzed using panel data fixed effect regression models through an econometric package, STATA 11.The study revealed a positive relationship between liquidity and bank-specific factors of size of bank and capital adequacy. The research findings also revealed that bank liquidity tends to decrease with higher loan growth, increase in non-performing loans and higher lending rate. The challenges of non-performing loans remain crucial to bank liquidity as it speeds up the deterioration of the advances book thereby increasing illiquid assets. The research recommends that banks adopt enhanced credit risk management techniques to minimize the effect of lending activity on liquidity. To promote prudent lending amongst Zimbabwean banks, the Central Bank is encouraged to enhance bank supervision and speed up the formation of a Credit Reference system. Finally, further research can take into consideration qualitative factors such as management efficiency changes in regulation or political incidences, salary and wages levels as probable determinants of liquidity in addition to the financial ratios.